2015
DOI: 10.1177/0895904815604217
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Bullying/Harassment Legislation and Educator Perceptions of Severity, Effectiveness, and School Climate: A Cross-Sectional Analysis

Abstract: In this cross-sectional study, we examined a matched sample of 924 educators' perceptions of severity of bullying and harassment and school climate prior to (Wave 1 n = 435) and following (Wave 2 n = 489) the implementation of New York's anti-bullying and harassment legislation, the Dignity for All Students Act (DASA). Alignment with DASA mandates predicted educator perceptions of (a) less severe bullying and harassment, (b) positive school climate, and (c) less need for improvement in school anti-bullying pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Since then, a series of pioneering longitudinal studies evaluating the outcome effectiveness of a Cognitive-behavioural Group Therapy intervention in reducing aggressive behaviour and peer victimization in school bulling have been gradually published. Moreover, the studies had generated research interests and discussions in other parts of the world as to effectiveness of Cognitive-behavioural Group Therapy intervention for anti-bullying programs [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a series of pioneering longitudinal studies evaluating the outcome effectiveness of a Cognitive-behavioural Group Therapy intervention in reducing aggressive behaviour and peer victimization in school bulling have been gradually published. Moreover, the studies had generated research interests and discussions in other parts of the world as to effectiveness of Cognitive-behavioural Group Therapy intervention for anti-bullying programs [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Legislation related to bullying does exist at the state level. Indeed, Cosgrove and Nickerson (2015) report that 49 states have enacted legislation to address bullying and harassment behaviors as of the date of their publication (p. 521).…”
Section: Bullyingmentioning
confidence: 99%
“…In response to this growing body of legislation, the Department of Education adopted a framework for states that they outlined in a "Dear Colleague" letter in December of 2010 (Stuart-Cassel et al, 2011). This framework includes a number of elements: definition of bullying behavior and protected groups; development and implementation of district policy; parameters for applying policies, including policy communication and recordkeeping; and monitoring of policies, procedures, actions and interventions that may be employed to prevent bullying (Cosgrove & Nickerson, 2015;Stuart-Cassel et al, 2011). In a study looking at the extent to which states implemented these suggested components, Stuart-Cassel and colleagues (2011) noted that only two states include all of the identified features.…”
Section: Bullyingmentioning
confidence: 99%
“…For example, 51% to 98% of educators reported that their school systems had adopted a local anti-bullying policy in compliance with their state's policy [60][61][62][63][64][65][66]. In terms of training and notification regarding bullying policies, 39% to 94% of educators reported receiving training on the policy [60,61,[64][65][66][67][68][69], and 56% to 84% of educators reported that students were notified about the policy [62,64,65,69,70]. Regarding school procedures, 60% to 94% of educators indicated that their school maintained procedures for reporting bullying [64,67,69,70], 78% to 92% of educators indicated that their school had procedures for investigating reports or complaints about bullying [65,67,69,70], and 52% to 80% of educators indicated that their school provided mental health assistance to students involved in bullying [61,65,69].…”
Section: Fidelity Of Implementation Of Anti-bullying Policiesmentioning
confidence: 99%
“…Only one study was found in the literature that examined the extent to which an anti-bullying policy was implemented and bullying outcomes [67]. This study found that higher levels of implementation of strategies associated with a state anti-bullying law predicted lower levels of bullying severity, lower levels of harassment based on protected classes (e.g., race, sex, national origin, religion, disability, weight, sexual orientation, and gender identity), and more positive perceptions of school climate [67]. Given that this was the only study found in the literature to examine fidelity of policy implementation with bullying outcomes, more research is needed in this area.…”
Section: Fidelity Of Implementation Of Anti-bullying Policiesmentioning
confidence: 99%